The archaeal and bacterial community structure in composted cow manures is defined by the original populations: a shotgun metagenomic approach - Romero-Yahuitl, Vanessa; Zarco-González, Karla Estephanía; Toriz-Nava, Ana Lilia; Hernández, Mauricio; Velázquez-Fernández, Jesús Bernardino; Navarro-Noya, Yendi E.; Luna-Guido, Marco; Dendooven, Luc (Frontiers in Microbiology, 2024)
Introduction Organic wastes are composted to increase their plant nutritional value, but little is known about how this might alter the bacterial and archaeal community structure and their genes. Methods Cow manure was collected from three local small-scale farmers and composted under controlled conditions, while the bacterial and archaeal communities were determined using shotgun metagenomics at the onset and after 74 days of composting. Results The bacterial, archaeal, methanogen, methanotrophs, methylotroph, and nitrifying community structures and their genes were affected by composting for 74 days, but the original composition of these communities determined the changes. Most of these archaeal and bacterial groups showed considerable variation after composting and between the cow manures. However, the differences in the relative abundance of their genes were much smaller compared to those of the archaeal or bacterial groups. Discussion It was found that composting of different cow manures did not result in similar bacterial or archaeal communities, and the changes that were found after 74 days were defined by the original populations. However, more research is necessary to determine if other composting conditions will give the same results.